Single Crystal Growth of Coumarin Dyes and Study of Their Electrical Conductivity - Christopher, V; Suhasini, K.P (International Journal of Chemistry and Materials Research, 2015)
Three coumarin derivatives i.e., 7-hydroxy-2H-1-benzopyran-2-one (umbelliferone) 3a, 4-methyl umbelliferone (C-4), 3b and 7-amino-4-methyl-benzopyran-2-one (C-120), 3c were synthesised by both conventional and microwave assisted synthetic methods and characterized. The pure compounds were initially grown into seeds (minute crystals having potential to grow into large crystals) and developed into single crystals using solution growth technique in a cryostat under careful monitoring. The desired single crystals were isolated and studied for their electrical conductivity properties by two terminal method. The results are promising and these pure organic compounds (coumarins) can act as promising semi-conductors.